Modifikasi Perilaku Terhadap Anak Trauma Bullying Melalui Metode Psikodinamik - Irhamni Rahman; Andrio Ramadhan; Fadhil Aryadi; Muhammad Abi Januar; Muhammad Andri Saputro (Departement of Mathematics Education, 2024)
Bullying, as a deliberate and repetitive form of aggression, can result in detrimental psychological, physical, and social impacts, occurring across various educational levels. This article aims to assist individuals affected by bullying trauma in their recovery, fostering self-confidence, and mitigating feelings of social inadequacy. The study emphasizes intervention employing a Biopsychosocial technique within the Psychodynamic method, utilizing the Operant Conditioning Theory (Skinner's Experiment). Through a planned and implemented ten-day intervention, behavioral modifications successfully attained the intended objectives. The client has been able to engage socially at least once a day for two weeks, with a duration of six hours per day, signifying success in addressing the repercussions of bullying and reintegration into their social milieu.